Pengaruh Jumlah Penduduk, Perdagangan Jasa dan Nilai Tukar Terhadap Pertumbuhan Ekonomi Di 7 Negara ASEAN Dalam Perspektif Ekonomi Islam Periode Tahun 2017-2024 - M. Gilang Prabowo; Anas Malik; Mia Selvina (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
This study aims to examine the effects of population, trade in services, and exchange rate variables on economic growth in seven ASEAN countries from 2017 to 2024. A quantitative research method was employed, utilizing secondary data obtained from the World Bank. A panel data model was applied in the analysis. The results from the panel data regression using the Common Effect Model indicate that the population variable (X1) has a negative but statistically insignificant effect on economic growth (Y). The export of services (X2) and import of services (X3) variables also show no significant impact on economic growth (Y). In contrast, the exchange rate variable (X4) has a positive and significant effect on economic growth (Y). However, the simultaneous F-test results reveal that population, trade in services, and exchange rates collectively do not have a significant effect on economic growth